2021
DOI: 10.3390/app11062631
|View full text |Cite
|
Sign up to set email alerts
|

Fire Safety Risk Analysis of Conventional Submarines

Abstract: Conventional (diesel-electric) submarines can provide improved stealth compared to nuclear submarines once submerged. This is because nuclear submarines are generally larger and are required to operate their nuclear reactors at all times, unlike diesel-electric submarines which are generally smaller and can run exclusively on batteries when submerged which generally requires fewer moving parts. These characteristics normally result in a smaller acoustic, thermal and magnetic signature which afford diesel-elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Inventions 2023, 8, x FOR PEER REVIEW 21 of 28 1 Using 2 neurons in the hidden layer. 2 Using 1 neuron in the hidden layer. 3 Excluding the operating point No.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Inventions 2023, 8, x FOR PEER REVIEW 21 of 28 1 Using 2 neurons in the hidden layer. 2 Using 1 neuron in the hidden layer. 3 Excluding the operating point No.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Apart from refrigeration and cryogenic applications, where the Stirling cycle has achieved remarkable developments [1], technological and commercial vicissitudes over more than two hundred years have restricted the current applications of the Stirling engine practically, to cases where there is less competition. These range from anaerobic underwater equipment [2] to the combined production of heat, cooling, and electricity, especially in systems powered by waste heat [3] and renewable energies on a low power scale [4][5][6][7]. Additionally, variants of the Stirling engine are among the alternatives being evaluated for power generation in space, both for space missions and for terrestrial use [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, the likelihood and severity of fire-related dangers linked with LIBs have been documented, with over 300 reported fires or fire-related events and 40 fatalities. 39 Combustion characteristics of LIB fires.-A LIB comprises four primary components: a cathode, an anode, a separator, and an electrolyte. Traditional cathodes typically comprise transition metal oxides, with natural graphite as the anode.…”
Section: Origin Of Libs Fire and Its Combustion Characteristicsmentioning
confidence: 99%
“…identify small satellite battery systems to ensure the reliability of BMS and LIBs and provide credibility for the use of LIBs in space applications [9]. In addition, Depetro et al observed that LIBs were likely to significantly improve the capability of conventional submarines [10].…”
Section: Et Al Conducted a Study Tomentioning
confidence: 99%